Relevansi Prinsip Hukum Ekonomi Syariah dalam Mewujudkan Kesejahteraan Buruh Industri Manufaktur Otomotif - Aldi Abdul Aziz; Ecep Ishak Fariduddin; Muflih Adi Laksono (SUPREMASI: Jurnal Pemikiran, Penelitian Ilmu-ilmu Sosial, Hukum dan Pengajarannya, 2026)
This study is motivated by the persistently low welfare of workers in the automotive manufacturing industry despite its role as a major pillar of the national economy. This condition reflects a gap between industrial growth and worker welfare. Islamic economic law offers principles of justice, balance, and social responsibility. The study analyzes the implementation of justice (‘adl), mutual assistance (ta’āwun), and the prohibition of exploitation (zulm) in improving worker welfare. Using a qualitative descriptive approach, the findings show that applying these principles enhances both material and spiritual welfare and fosters more equitable, harmonious industrial relations in the automotive manufacturing sector.